Technical, economic, and environmental assessment of liquid fuel production on aircraft carriers. (15th December 2019) - Comidy, Liam J.F.; Staples, Mark D.; Barrett, Steven R.H.
Highlights: Technologies and scenarios for fuel production on aircraft carriers are assessed. Tradeoffs between fuel cost, climate impacts and thermal efficiency are shown. Fuel costs range from 1.91 to 4.49/L, compared to 1.39/L for petroleum fuel. Plant mass and volume are significant, and may impede integration with ship design. Abstract: The supply chain to deliver fuels to aircraft carriers is complex, dangerous, and expensive, and one option to mitigate these risks is to produce fuel at sea. This work quantifies the costs, climate impacts, and physical characteristics of three technology pathways for fuel production onboard aircraft carriers: alkaline electrolysis and reverse water gas shift (AE + RWGS); solid oxide electrolysis and RWGS (SOEC + RWGS); and co-electrolysis of steam and CO2 . Two design scenarios are evaluated: a small, infrequently operating plant using excess nuclear power (Scenario A); and a large, frequently operating plant with dedicated nuclear capacity (Scenario B). Fuel production costs are quantified using a Monte Carlo techno-economic analysis, ranging from 1.91 to 4.49 and 3.25–4.23 /L in Scenarios A and B, respectively. The lowest cost technology pathway is AE + RWGS. All technology pathways are shown to offer reductions in life cycle greenhouse gas emissions of 82–86% relative to petroleum JP-5. In Scenario B, the plant volume and weight are estimated at 50–67% and 432% of current aircraft carrier designs, respectively, highlighting challenges for technical feasibility. Furthermore, increasing plant production capacity and capacity factor is shown to reduce the unit cost of fuel production, but that this is largely offset by the additional costs of dedicated nuclear capacity required at larger scales. The results indicate that fuel production on an aircraft carrier may be technically feasible, cost competitive, and environmentally beneficial relative to the petroleum fuels currently in use. However, research to further reduce system cost, weight, and volume, including experimental validation, are still required.